Application of strategic stockpile for ore quality stabilization at Erdenet open pit mine - Batsukh Elbegzaya; Sodnom Tsedendorj; Battogtokh Batbold; Borya Orkhontuul (Mongolian Geoscientist)
Ore mixing and blending are performed at the mining benches, typically involving 6-8 working benches. However, as the mine deepens, operations across multiple benches become more challenging, and declining copper grades necessitate increased processing plant capacity. Variability in total copper content in the sulfide ore can reach up to 8%, with an allowable range of 0.541% to 0.461% when the average is 0.501%, as per internal Erdenet standard STP-01352-901908085-11:2013. Maintaining this standard within a 24-hour period is difficult, complicating process control. To achieve an 85% metal recovery rate, the processing plant is adjusted to meet the standard ore quality. However, short-term fluctuations exceeding ±8% lead to decreased recovery rates and potential metal loss. Establishing tactical stockpiles close to the primary crushers or along transportation routes can mitigate these issues by stabilizing ore quality before processing. The tactical stockpile project relies on optimizing operational procedures, integrating stockpile construction using mine-sourced waste rock, preparing platforms, utilizing existing equipment capacity, enhancing signage and lighting, and creating guidelines for safe operation and grade averaging. This approach provides a rapid and effective solution to improve blending efficiency and operational stability.